Detective knight. Redemption [videorecording (DVD)] - Large, Corey; Large, Corey; Drake, Edward; Willis, Bruce, 1955-; Munro, Lochlyn, 1966-; Mirchoff, Beau, 1989-; Edwards, Miranda; Johansson, Paul, 1964- (Lionsgate, 2023)
In custody in New York, Knight finds himself in the middle of a jailbreak led by The Christmas Bomber, a brutal fanatic whose Santa Claus disciples are terrorizing the city. With the promised return of his badge in exchange for taking out the terrorists, the steely-eyed Knight doles out mercy for the just and merciless justice for all the rest.